2012
DOI: 10.1002/jccs.201100482
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline/SiO2 Nanocomposite Catalyzed Efficient Synthesis of Quinoxaline Derivatives at Room Temperature

Abstract: Polyaniline/SiO 2 nanocomposite material has been synthesized by using chemical oxidative method. Prepared catalytic material was characterized by means of transmission electron microscopy (TEM), thermal analysis (TG-DTA), X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and Fourier transform infrared spectroscopy (FT-IR). Solvent stability for the catalyst has been screened using UV-Visible spectroscopy. Polyaniline/SiO 2 catalyzed route has found to be an effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…According to Yelwande et al [47] the polyaniline/SiO 2 catalysed technique has been found to be an effective and rapid precursor for the fabrication of quinoxaline derivative 106 by cyclocondensation of 1,2-diketones 104 and o-phenylenediamines 105 at room temperature. The catalyst's reusability was tested across three runs and it was discovered that the catalyst retains its activity even after the third run (Scheme 39, Table 26).…”
Section: Chemistryselectmentioning
confidence: 99%
“…According to Yelwande et al [47] the polyaniline/SiO 2 catalysed technique has been found to be an effective and rapid precursor for the fabrication of quinoxaline derivative 106 by cyclocondensation of 1,2-diketones 104 and o-phenylenediamines 105 at room temperature. The catalyst's reusability was tested across three runs and it was discovered that the catalyst retains its activity even after the third run (Scheme 39, Table 26).…”
Section: Chemistryselectmentioning
confidence: 99%
“…Polyaniline/SiO 2 nanocomposite material was prepared and it was used as a catalyst for the synthesis of quinoxalines. They reported that 10% catalyst was found to be optimal for the reactant transformation, and the catalyst activity was found to be consistent even after three runs [36]. Another popular method to synthesize quinoxalines is by using TiO 2 nanoparticles as a catalyst.…”
Section: Application Of Nanoparticles In Organic Synthesismentioning
confidence: 99%
“…In continuation of our interest towards the development of new heterogeneous catalyst for the synthesis of bioactive heterocyclic [55][56][57][58][59][60][61], herein we wish to report for the first time a simple, non-toxic and efficient methodology for the synthesis of 3,4-dihydropyrimidin-2(1H)ones in moderate to good yields by the reaction of benzaldehydes, β-ketoesters and urea/ thiourea using polyaniline/SiO2 as catalyst (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%